Perception of medical undergraduate students about teaching learning methods and assessment tools used in a medical college in India - Singh, Arun; Katyal, Rashmi; Chandra, Shalini; Joshi, Hari S.; Singh, Kashmir (International Journal Of Community Medicine And Public Health, 2017)
Background: New teaching-learning methods and assessment tools can be used to enhance the learning among the medical students. But their views are important for the faculty members who are holding the decision making posts. Methods: The duration of teaching session was 2 hours 5 minutes using six teaching-learning methods. Out of total 119 students the perception and level of awareness of 96 students were recorded about the six teaching-learning methods and five assessment tools in the pre and post-tests. Descriptive analysis was done. The students paired “t” and ANOVA were used for statistical analysis and “p” value <0.05 was taken as statistically significant. Results: Vertical integration was strongly agreed upon as the best method and among the three traditional teaching methods the case demonstration was the most liked method of teaching by the students and. Among the interactive teaching methods, the case based learning was the most liked method by the students. Out of total five assessment tools the MCQs was the most liked. Similarly, OSCE and DOPS were considered to be better assessment tools as compared to others (P-value significant being <0.05). Conclusions: Vertical integration will be more helpful in real professional life scenario than in passing the exams which should be incorporated in medical curriculum.